Retention of zirconia crowns to titanium bases with straight versus angled screw access channels: an invitro study - Eman Assem Ibrahim; Mohamed Moataz Khamis; Salah Ezzelarab; Ahmed M. Abdelhamid (BMC, 2023)
Abstract Background The aim of this study was to assess the impact of abutments with angled screw access channel on the retention of zirconia crowns. Methods Seven implant replicas were inserted in epoxy resin blocks. Fourteen zirconia crowns for central incisor tooth were digitally fabricated and cemented to titanium bases (Ti-bases) with resin cement. Titanium bases were categorized into 2 groups (n = 7). Control group (Group STA) included straight screw access channel abutments. Study group (Group ASC) included angled screw access channel abutments. Following aging (5 °C-55 °C, 60 s; 250,000 cycles, 100 N, 1.67 Hz), the pull-off forces (N) were recorded by using retention test (1 mm/min). Types of failure were defined as (Type 1; Adhesive failure when luting agent predominantly remained on the Ti-base surface (> 90%); Type 2; Cohesive failure when luting agent remained on both Ti-base and crown surfaces; and Type 3; Adhesive failure when luting agent predominantly remained on the crown (> 90%). Statistical analysis was conducted by using (IBM SPSS version 28). Normality was checked by using Shapiro Wilk test and Q-Q plots. Independent t-test was then used to analogize the groups. Results Mean ± standard deviation of retention force records ranged from 1731.57 (63.68) N (group STA) to 1032.29 (89.82) N (group ASC), and there was a statistically significant variation between the 2 groups (P < .05). Failure modes were Type 2 for group STA and Type 3 for group ASC. Conclusions The retention of zirconia crowns to abutments with a straight screw access channel is significantly higher than abutments with angled screw access channel.